Coupling career fairy tale “Fascinating Sociology Class”. How to teach sociology? The sociology of sociology - Wagner, Izabela (Qualitative Sociology Review, 2009)
This paper is a simple account of my teaching experience1, the aim of which is to answer the question: “How can we successfully teach interactionism, labeling theory, grounded theory and other sociological bases related to qualitative methods with the active participation of students?”. Through the examples of sociologists working in the Chicago Tradition, French sociologists working with Pierre Bourdieu, and other examples from American sociology, I show that sociological work is group activity. It is argued in this paper, that to make sociological thinking understandable to students teachers may do well to contextualize key theorists in their narrative/biographical context. The students learn, that sociologists are not magicians or genius individuals who produce attractive theories. Rather, they work in collaboration with other humans to generate knowledge. Moreoever, I demonstrate that sociologists’ contributions are often strongly related to and influenced by their broader life context.